The Role of the Armed Forces in Egypt’s Political System - I. A. Chaiko (Vestnik MGIMO-Universiteta, 2013)
The article offers an analysis of the status and position of the army, as the key institution within Egypt’s political system, showing the path and degree of its transformation as a result of the Arab Spring revolutionary wave affecting Egypt among other countries of the Arab world. It also contains certain forecasts concerning the future role of the Egyptian military, with the author, however, deeming the status of the army in the new political situation as being anything but stable and definitive.